History of the British West Indies. - Burns, Alan, Sir, 1887-1980. (London, Allen & Unwin, 1954)
Volgens [CU02] beschikken zij over 2 ex.
With 13 appendices, index of persons and general index
Includes bibliographical references (pages 769-780).
NLJCols20082021
Keywords: West Indies, British -- History; Antilles britanniques -- Histoire; West Indies -- British West Indies; West Indies -- History; Antilles britanniques - Histoire; History